Pengaruh Karakteristik Siswa Terhadap Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran IPS Kelas IX SMP Swasta Talitakum Medan - Purba, Ika Lovika; Siahaan, Nova Yunita Sari; Manullang, Dapot Tua (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the influence of student characteristics on critical thinking skills in social studies for grade IX at Talitakum Private Junior High School in Medan. This research is quantitative and uses the survey method. The study was conducted at Talitakum Private Junior High School in Medan with a population of 25 students. The sample in this study was taken using the total sampling method. The data collection techniques used were documentation and questionnaires. The prerequisite tests used were normality test and homogeneity test, while the data analysis techniques used were descriptive statistical analysis, t-test (for partial hypothesis testing), and the coefficient of determination (R2). The research results indicate that visual (X1), auditory (X2), and kinesthetic (X3) learning styles have a partial effect on critical thinking skills (Y) with t-calculated values greater than the t-table values for the variabels (X1) (4.946>1.720), (X2) (4.768>1.720), and (X3) (1.686>1.720). Thus, it can be concluded that there is an influence of students' characteristics on critical thinking skills in social studies for ninth-grade students at SMP Swasta Talitakum Medan.